Factors Influencing the Use of ICT for English Language Learning of Indonesian EFL University Students - Arif, Tubagus Zam Zam Al; Handayani, Reli (Elsya : Journal of English Language Studies, 2022)
This study examines the factors of the Technology Acceptance Model (TAM) that influence the acceptance of ICT use for English language learning of EFL University Students. This study also addresses the possible obstacles that affect and limit the use of ICT by adding motivation and ICT skills as extended TAM variables. This area of research topic is unexplored in the Indonesian context, especially in higher education institution. An analysis of these factors can assist instructors to understand how students learn using ICT and in providing useful advice to them during the learning process. The quantitative method was applied in this study, which included 303 students' teachers of English Education at a state university in Jambi, Indonesia. The instrument used in collecting the data was an online questionnaire. Data collected were analyzed by using Structural Equation Modeling (SEM) with SmartPLS3 program to analyze the proposed hypotheses formed in order to meet the study objectives. The SEM result indicated that the factors of the technology acceptance model are the main factors affecting the ICT use. The study concluded that the influence of motivation and skills for ICT usage was mediated by three main TAM variables, namely perceived ease of use, perceived usefulness, and attitudes.